(Not) Sharing the Fruits of Growth: The Impact of Governments and Markets on Living Standards in Germany, the Netherlands, and the United States - Bruce Headey; Stephen Headey; Ruud Muffels (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper reviews changing income distributions in the United States, Germany, and the Netherlands, treating the three countries as leading economic performers in ' the three worlds of welfare capitalism.' Previous analyses have shown that earnings dispersion is increasing. The potential impact of government through the tax and transfer system has been largely ignored. It is shown that in the United States and Germany changes in market incomes favored the upper quintiles and that the bottom quintile became worse off. Government did nothing to reverse these trends. In the Netherlands the trend in market incomes was similar but the government redistributed, so that the bottom quintile' s post-government income increased along with the other quintiles. Data come from the PSID-GSOEP Equivalent File and the Dutch Socio-Economic Panel.
Keywords: 330; Sozialstaat; Wirtschaftswachstum; Einkommensverteilung; Einkommensumverteilung; Lebensstandard; Verteilungspolitik; Vergleich; Deutschland; Niederlande; USA